2011
DOI: 10.1007/s10509-011-0791-x
|View full text |Cite
|
Sign up to set email alerts
|

The Landau level-superfluid modified factor and the overal soft X/γ-ray efficiency coefficient of a magnetar

Abstract: As soon as the energies of electrons near the Fermi surface exceed Q, the threshold energy of inverse β-decay, electron capture (EC) dominates inside a neutron star. The high-energy neutrons released by EC will destroy anisotropic 3 P 2 neutron Cooper pairs in the degenerate superfluid. By colliding with the neutrons produced in the process n + (n ↑ n ↓) → n + n + n, the kinetic energies of the neutrons released by EC will be transformed into thermal energy. A portion of this thermal energy will be transported… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Dong et al (2014)) found that both “outliers” of BH XRBs and bright AGNs follow a steeper fundamental plane of black hole activity. Coriat et al (2011) argued that the two fundamental planes are regulated by radiatively inefficient (e.g., ADAF) and radiatively efficient accretion processes (e.g., SSD + corona), respectively, if we assume the jet launching and radio radiation behave identically (see also, Deng et al 2020; Gao et al 2011a; Fu et al 2020; Li et al 2016; Zhu et al 2016; Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al (2014)) found that both “outliers” of BH XRBs and bright AGNs follow a steeper fundamental plane of black hole activity. Coriat et al (2011) argued that the two fundamental planes are regulated by radiatively inefficient (e.g., ADAF) and radiatively efficient accretion processes (e.g., SSD + corona), respectively, if we assume the jet launching and radio radiation behave identically (see also, Deng et al 2020; Gao et al 2011a; Fu et al 2020; Li et al 2016; Zhu et al 2016; Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However there is a serious mistake in their calculation. They use the following method to calculate the statistical weight (degeneracy) of the Landau level n. The possible microscopic state number density in the interval of momentum p z → p z + dp z along the magnetic field direction for the electron gas is given by (10) In their calculation. The result of the microscopic state number for the level (n +1) in the plane perpendicular to magnetic field is essentially equal to the area of the torus between (See Fig.2).…”
Section: A Misleading Approach Regarding the Fermi Energy Of The Elecmentioning
confidence: 99%
“…Following is how they calculate the number of microscopic states: the number density of microscopic states is , (11) by using Eq. (10). According to the Pauli Exclusion Principle, the number density of microscopic states is equal to electrons number density in a complete degenerate electron gas, , where Y e and ρ are electron fraction (5-8%) and mass density.…”
Section: A Misleading Approach Regarding the Fermi Energy Of The Elecmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fermi energy of relativistic electrons E F (e) is one of most important and indispensable physical parameters in the EoS, and varies with matter density ρ. The electron Fermi energy influences directly weak-interaction processes including modified URCA reactions 4 , electron capture 5,6,7,8,9 and so on, in the circumstance of a NS. These influences will change intrinsic EoS, interior structure and heat evolution, and even affect the whole properties of the star.…”
Section: Introductionmentioning
confidence: 99%